2016
DOI: 10.1063/1.4940662
|View full text |Cite
|
Sign up to set email alerts
|

Solid-state conversion of (94-x)(Na1/2Bi1/2)TiO3-6BaTiO3-x(K1/2Na1/2)NbO3 single crystals and their enhanced converse piezoelectric properties

Abstract: (94-x)(Na1/2Bi1/2)TiO3-6BaTiO3-x(K1/2Na1/2)NbO3 (NBT-6BT-xKNN) piezoelectric ceramics have notable potential for replacing lead containing piezoelectric ceramics in actuator applications due to their exceptionally large strain. However, a high electric field for producing a large strain and a large hysteresis are critical issues that should be resolved for practical actuator applications. In an attempt to address these issues and optimize the piezoelectric performance, we fabricated NBT-6BT-xKNN (x = 0 - 5) pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The properties of the polycrystalline NBT-25ST sample are comparable to those previously measured [3,11]. Compared with the polycrystalline sample, the (001)-oriented single crystal shows lower coercivity E c , increased saturation polarization P s , remnant polarization P r and maximum strain S max , an increase in S max /E max of 41% and a reduced strain hysteresis ΔS/S max of 18%, where ΔS is the difference in strain between the upper and lower parts of the curve when E = maximum electric field E max /2 [38]. The S max /E max value of the (001)-oriented NBT-25ST single crystal sample is comparable to those of (Na 1/2 Bi 1/2 )TiO 3 -BaTiO 3 -(K 0.5 N 0.5 )NbO 3 single crystals [38,44].…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The properties of the polycrystalline NBT-25ST sample are comparable to those previously measured [3,11]. Compared with the polycrystalline sample, the (001)-oriented single crystal shows lower coercivity E c , increased saturation polarization P s , remnant polarization P r and maximum strain S max , an increase in S max /E max of 41% and a reduced strain hysteresis ΔS/S max of 18%, where ΔS is the difference in strain between the upper and lower parts of the curve when E = maximum electric field E max /2 [38]. The S max /E max value of the (001)-oriented NBT-25ST single crystal sample is comparable to those of (Na 1/2 Bi 1/2 )TiO 3 -BaTiO 3 -(K 0.5 N 0.5 )NbO 3 single crystals [38,44].…”
Section: Resultsmentioning
confidence: 97%
“…Some NBT-BT single crystals with compositions near to the morphotropic phase boundary between rhombohedral and tetragonal phases exhibit a high S max /E max and free strain such as 0.945(Na 1/2 Bi 1/2 )TiO 3 -0.055BaTiO 3 , with S max /E max ≈ 1420 pm/V and 0.44% strain, and Na 1/2 Bi 1/2 TiO 3 -Ba(Ti,Zr)O 3 , with S max /E max ≈ 2000 pm/V and 0.45% strain [35][36][37]. Single crystals of (Na 1/2 Bi 1/2 )TiO 3 -BaTiO 3 -(K 0.5 N 0.5 )NbO 3 (NBT-BT-KNN) compositions showed a giant strain of 0.57% and S max /E max of 950 pm/V [38] and a giant strain of 0.83% at an electric field of 28 kV/cm [39]. Single crystals of NBT-25ST may also have improved piezoelectric properties, but as of yet only limited work on single crystal growth in this system has been reported and the electrical properties have not been measured [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The grown single crystal exhibited good piezoelectric properties which were comparable to those of other lead-free single crystals. The same group of authors continued their research on the same material [64] and 2 years later reported their finding that the KNN content in NBT-BT-KNN had a significant effect on the piezoelectric properties of NBT-BT-KNN single crystals. Along with that, they were able to demonstrate that the SSCG method was a prospective method for growth of NBT-BT-KNN single crystals with high performance, which could replace Pb(Zr,Ti) O 3 for actuator applications.…”
Section: Nbt-based Lead-free Single Crystalsmentioning
confidence: 94%